Leadership and competition in the age of public and private school markets. Issue 3 (21st September 2020) - Reimann, Carolin Julia; Schwarz, Judith; Koinzer, Thomas
Abstract : Purpose: The article deals with competition between primary schools in Berlin. The focus is on the perception of competition and the process of student selection – despite school law restrictions for primary state schools. The aim is to find out whether and in what way primary school leaders perceive a competitive situation and how they act in view of second-order competition. Design/methodology/approach: Berlin primary school leaders' statements were analyzed, which were collected and evaluated using quantitative and qualitative methods. Findings: Results show that schools with a good reputation are more likely to benefit from competition because a good reputation may increase the demand for spots at that school and may enable the school to select "desirable" students. State school leaders are more limited in their actions, while private school principals are more autonomous and are better able to make a match between a school's orientation and families' ideas. Research limitations/implications: The study is limited by its small sample size, yet it provides a basis for further research and gives much needed attention to selection processes at primary schools in Germany. Originality/value: This is one of a few studies looking at the perspectives of primary school leaders regarding the competitive situation and in particular the selection of students.